PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI, DAN AKUNTABILITAS PUBLIK TERHADAP KINERJA SATUAN KERJA PERANGKAT DAERAH (SKPD) KOTA AMBON - Rita J. D. Atarwaman (Soso-Q : Jurnal Manajemen, 2017)
This study aims to obtain empirical evidence about the Influence of Organizational Culture, Organizational Commitment, and Public Accountability on the Performance of Regional Work Unit (SKPD) in the Ambon City Government Environment. This research is a survey research using a questionnaire, in which questionnaires are given directly to SKPD employees in several departments in the Ambon City Government Environment. Data analysis uses Multiple Linear Regression. The results showed that the Organizational Culture variable had a positive effect on SKPD performance. The variable Organizational Commitment has no influence on the SKPD Performance and the Public Accountability variable also has no influence on SKPD Performance. Keywords: Organizational Culture, Organizational Commitment, Public Accountability, Organizational Performance